CD36 haplotypes are associated with lipid profile in normal-weight subjects - Ramos-Arellano, Luz E (BioMed Central, 2013)
BACKGROUND: Dyslipidemia is a common metabolic disorder that may result from abnormalities in the synthesis, processing and catabolism of lipoprotein particles. Disorders of lipoprotein concentrations and elevated concentration of oxidized lipoproteins (oxLDL) are risk factors in the pathogenesis of cardiovascular diseases (CVD). CD36 plays an important role in lipid metabolism and polymorphisms in the CD36 gene are related to cardiovascular risk factors. The purpose of this study was to evaluate whether there is an association between genotypes and haplotypes of five polymorphisms in the CD36 gene with lipid levels in young normal-weight subjects. METHODS: A total of 232 unrelated subjects with normal-weight of 18 to 25 years old (157 women and 75 men) were randomly selected. The lipid profile and glucose levels were measured by enzymatic colorimetric assays. Genotyping of the polymorphisms -33137A/G (rs1984112), -31118G/A (rs1761667), -22674 T/C (rs2151916), 27645 Ins/Del (rs3840546) and 30294G/C (rs1049673) in the CD36 receptor gene was performed by polymerase chain reaction and restriction fragment length polymorphism, linkage disequilibrium analysis among the five polymorphisms and an analysis of haplotype were estimated. RESULTS: HDL-C levels was lower in men than in women (P = 0.03). However, the median oxLDL levels in men was higher than in women (P = 0.05). There was no significant difference in the levels of TC, TG, LDL-C and glucose (P > 0.05). HDL-C levels were lower in the subjects with TC genotype of polymorphism -22674 T/C (P = 0.04), but the carriers of TT genotype had lower oxLDL levels (P = 0.01). LDL-C levels were higher in young carriers of CC genotype for 30294G/C polymorphism than non-carriers (P = 0.03). The subjects carrying the AATDC haplotype had 3.2 times presumably higher risk of LDL-C > 100 mg/dL than the carrying the AGTIG haplotype (P = 0.02), whereas the subjects carrying the AATIC haplotype had 2.0 times presumably higher risk of TC > 200 mg/dL than the carrying the AGTIC haplotype (P = 0.02). CONCLUSION: The study provides evidence of a genetic association of CD36 haplotypes with the variability in LDL-C and TC levels in a sample of normal-weight subjects.